Virtue and Knowledge. (28th March 2016) - Carr, David
Abstract: In the Nicomachean Ethics Aristotle distinguishes fairly sharply between the practical deliberation of moral virtue and the epistemic reflection of theoretical or truth-focused enquiry. However, drawing on insights from Plato and Iris Murdoch, the present paper seeks a more robust epistemic foundation for virtuous deliberation as primarily grounded in clear or correct perception of the world and human association, character and conduct. While such perception may not be sufficient for moral virtue, it is here argued that it is necessary. Murdoch's view that literature may afford especially effective correction of moral misperception is also supported by appeal to literary examples.